The faculty evaluation scheme in schools and colleges of nursing in Iloilo City - Flores, Cecilia A. 1944- (1976)
This is a study of the faculty evaluation scheme in the schools and colleges of nursing in Iloilo City, namely: Governor Benito Lopez Hospital School of Nursing; Iloilo Doctor's Hospital of Nursing; St. Paul's College of Nursing; University of San Agustin COllege of Nursing and Central Philippine University College of Nursing. The method used was the descriptive survey with the questionnaire-checklist and the interview schedule as the major tools. In general the schools of nursing in Iloilo City have an organized evaluation program that is functioning which indicates that the schools recognize the importance of evaluation and have made positive use of its results. However, a few of these schools do not have an operational evaluation program for its faculty.
Appendices: leaves 108-132
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Teachers, Rating of; Nursing schools; Performance standards